Surficial geomorphic expressions along the Zanskar shear zone (ZSZ), NW Himalaya, India - Omar Jaan Paul; Khalid Omar Murtaza; Malik Zubair Ahmad; Irfan Maqbool Bhat; Feroz Ahmad; Jehangeer Ahmad Mir; Waseem Qader; Suhail Hussain Sheikh; Shakil Ahmad Romshoo; Reyaz Ahmad Dar (Quaternary Science Advances)
There is substantial evidence of the dynamic interplay between surficial geomorphic processes and active tectonics in the Zanskar Shear Zone (ZSZ), northwest Himalaya, India. The ZSZ is a result of tectonic conversion with a SW–NE orientation that began in the Late Cretaceous and became stronger in the Early Miocene as a result of the collision of the Indian and Eurasian plates. Earlier studies have addressed its tectonic activity and metamorphic activation. However, the contribution of active tectonics to the geomorphic evolution of the region is less understood. Using the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) and Google Earth Imagery, various geomorphic features viz., alluvial fans, triangular facets, wineglass valleys, mountain fronts, knickpoints, and river terraces were identified and delineated. The study area was divided into three river sections viz., Suru, Doda, and Tsarap, running along or occasionally cutting across the strike of the ZSZ. The longitudinal river profiles suggest a relatively higher degree of tectonic activity along the Doda River, followed by the Tsarap and Suru Rivers. This spatial variation in the tectonic activity is also evident from the mountain front sinuosity index, wineglass valley index, triangular facets, and the morphometry of alluvial fans. Both the geomorphic features and morphometric parameters provide evidence of relative variation in the ZSZ activity along the Suru, Doda, and Tsarap River sections. Therefore, the present geomorphic evaluation suggests that the surficial (Quaternary) geomorphology documents the tectonic activity and its spatial variations along the ZSZ.